The Concept of Corporate Social Responsibility in Higher Education Institutions in Perspective Ketadulakoan - Mohammad Iqbal BAKRY; Muliati MULIATI; Jurana JURANA; Muhammad RIDWAN (International Journal of Environmental, Sustainability, and Social Science, 2024)
This research aims to reconstruct the concept of Corporate Social Responsibility (CSR) in Higher Education Institutions (or University Social Responsibility) from a religious perspective. The Critical Paradigm is used as a paradigm for developing this research. Interviews, observation and documentation carried out data collection. Informants were selected based on the credibility of the researcher. Data analysis was carried out by reconstructing the concept of CSR in higher education institutions (USRs) based on religious values. The findings of this research are the philosophy of Tadulakoan to dismantle the values ??of secularism, materialism and individualism in the implementation of USR in Tadulako. The research results found accountability in the form of reporting related to 1) Level of courage (Natona Nalanggai) in fighting for justice to achieve peace, 2) Ability to achieve success through collaboration of various intelligences, 3) Fighting power in achieving success. 4) Excellence (Nabaraka) in creating innovations to ease human life. 5) Accuracy and caution (Nompangila) in decision-making. 6) Obedience and loyalty (Natuvu No Sangata) to leaders who fulfill their mandate. 7) Level of democracy in joint decision-making activities, 8) Awareness in protecting community interests and the environment. This research can be one of the research that supports and is in line with the Strategic Plan and research road map achieved by Tadulako University (UNTAD).